The Bologna process in the context of teacher education – the case of master’s cycle in pre-school and primary school education - Pereira, Cristina (2012)
The present legislation concerning Professional Qualifications for Teaching (Law n.437, 2007) was created in the context of the Higher Education reorganization according to the Bologna Process. By situating the professional qualification of preschool teachers and primary school teachers at the second cycle level (Master’s), this law may contribute to reinforce the recognition of these actors‟ importance in the promotion of quality development, which is so necessary in the Portuguese society, and necessarily refers to the need of a demanding, qualitative initial teacher education. Having this context as background, the present communication intends to present and analyse some of the foundations of the curriculum organization for the Master’s Cycle in Pre-School and Primary School Education from the Castelo Branco School of Education, giving special attention to the integration of educational research methodologies in supervised teaching practice. Whereas the “voice” of the master’s is a fundamental tool for the analysis we want to achieve, we conclude with the presentation and analysis of results obtained with the administration of the experimental version of the questionnaire “Conceptions of Research Process and Teaching Practice” and the “Reflective Report” asked students in the final phase of the curricular component of the course.